Answer:
A) 7.37 x 10^-4 N
B) The resultant force will be towards the -x axis
Explanation:
The three masses have mass = 3500 kg
For the force of attraction between the mass at the origin and the mass -100 cm away:
distance r = 100 cm = 1 m
gravitational constant G= 6.67×10^−11 N⋅m^2/kg^2
Gravitational force of attraction [tex]F_{g}[/tex] = [tex]\frac{Gm^{2} }{r^{2} }[/tex]
where G is the gravitational constant
m is the mass of each of the masses
r is the distance apart = 1 m
substituting, we have
[tex]F_{g}[/tex] = [tex]\frac{6.67*10^{-11}*3500^{2} }{1^{2} }[/tex] = 8.17 x 10^-4 N
For the force of attraction between the mass at the origin and the mass 320 cm away
distance r = 320 cm = 3.2 m
[tex]F_{g}[/tex] = [tex]\frac{Gm^{2} }{r^{2} }[/tex]
substituting, we have
[tex]F_{g}[/tex] = [tex]\frac{6.67*10^{-11}*3500^{2} }{3.2^{2} }[/tex] = 7.98 x 10^-5 N
Resultant force = (8.17 x 10^-4 N) - (7.98 x 10^-5 N) = 7.37 x 10^-4 N
B) The resultant force will be towards the -x axis